Hulk (2008), volume 1 ebook Red hulk. - Loeb, Jeph (Hulk (2008), 2011)
Collects Hulk (2008) #1-6. When one of the Hulk's oldest associates is murdered, everyone turns to the team of Iron Man, She-Hulk and Leonard Samson to solve the case. All the evidence points to the Hulk as the killer, but all is not as it seems! Author: Jeph Loeb. Illustrator: Ed McGuinness. © 2020 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com